2007
DOI: 10.1136/oem.2007.035303
|View full text |Cite
|
Sign up to set email alerts
|

Exposures and reported symptoms associated with occupational deployment to the Buncefield fuel depot fire, England 2005

Abstract: Increased reporting of symptoms close to the fire during the burn phase was consistent with increased exposure to products of combustion, although no major acute illness was reported. That only a minority of individuals used face masks, which were not protective for symptoms, raises questions about the availability of adequate respiratory protection for such incidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that ocular symptoms are a frequent finding in people exposed to the smoke generated by fires, including wildfires (12)(13)24) . During the acute episode, the patients who attended the hospital emergency room and the healthy volunteers experienced ocu lar symptoms, an increase in bulbar conjunctival hyperemia, and a reduction in TBUT values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that ocular symptoms are a frequent finding in people exposed to the smoke generated by fires, including wildfires (12)(13)24) . During the acute episode, the patients who attended the hospital emergency room and the healthy volunteers experienced ocu lar symptoms, an increase in bulbar conjunctival hyperemia, and a reduction in TBUT values.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 8 hours average value was greater than the standard value recommended by the WHO Air Quality Guidelines (AQG) established by the World Health Organization (22) in 29 opportunities. For NO 2 and PM, average levels are usually not exceeding 50% of the maximum levels recommended by the WHO, but during the acute episode, the concentrations were twice as high as those recommended in the WHO guidelines (23)(24) .…”
Section: Pollutant Levelsmentioning
confidence: 99%
“…24 A risk assessment approach for blood borne infections and tetanus following bombings and mass-casualty events subsequently has been published by the Centers for Disease Control and Prevention. 25…”
Section: Limitationsmentioning
confidence: 99%